ӨМНӨД МОНГОЛЫН БАРУУННАРАН НҮҮРСНИЙ ОРДЫН ТАВАНТОЛГОЙ ФОРМАЦЫН ЭЛСЭН ЧУЛУУНЫ ГЕОХИМИЙН СУДАЛГАА - Л., Жаргал; Б., Дэмбэрэлсүрэн; Б., Мөнхцэнгэл (Geological Issues, 2022)
Baruunnaran coal deposit is located in southern Mongolia and belongs to Tavantolgoi coal zone of South Gobi Basin. Coal seams are hosted in the middle Permian Tavantolgoi Formation, which is subdivided into lower and upper member based on lithological characteristics. Ten sandstone samples collected from exploration drill holes. The provenance, paleoweathering and paleoclimate of coal-bearing Tavantolgoi Formation were studied by geochemistry. The sandstone samples were depleted in Ca, Na, Ka, Ba, Rb, Sr and enriched in Si and Al compared with Upper Continental Crust (UCC). Low values (0.28-0.75) of the index of compositional variability in sandstone compared with Post-Archean Australian Shale (PAAS-0.85) suggest a mature source of Tavantolgoi Formation. Chemical Index of Alteration (CIA) values of the samples from the lower member range from 74 to 85, indicating moderate to intense weathering condition in source rock. The CIA values of samples from the upper member range from 65 to 71, indicating weak to moderate weathering condition in source rock. Also, the sandstones were deposited during semi-moist to semiarid paleoclimate condition. Immobile trace elements ratios (Th/Sc, Zr/Sc, Ce/Sc, Ti/Zr) indicate that the sandstones were sourced fromandesite, dacite to rhyolite.